Thinking about dementia : culture, loss, and the anthropology of senility - Leibing, Annette; Cohen, Lawrence, 1961- (Studies in medical anthropology., 2006)
Cultural responses to most illnesses differ; dementia is no exception. These responses, together with a society's attitudes toward its elderly population, affect the frequency of dementia-related diagnoses and the nature of treatment. Bringing together essays by nineteen respected scholars, this unique volume approaches the subject from a variety of angles, exploring the historical, psychological, and philosophical implications of dementia. Based on solid ethnographic fieldwork, the essays employ a cross-cultural perspective and focus on questions of age, mind, voice, self, loss, temporality, memory, and affect. Taken together, the essays make four important and interrelated contributions to our understanding of the mental status of the elderly. First, cross-cultural data show the extent to which the aging process, while biologically influenced, is also very much culturally constructed. Second, detailed ethnographic reports raise questions about the behavioral criteria used by health care professionals and laymen for defining the elderly as demented. Third, case studies show how a diagnosis affects a patient's treatment in both clinical and familial settings.; Finally, the collection highlights the gap that separates current biological understandings of aging from its cultural meanings. As Alzheimer's disease and other forms of dementia continue to command an ever-increasing amount of attention in medicine and psychology, this book will be essential reading for anthropologists, social scientists, and health care professionals.